A large infected urachal mass in an adult: A case report in Tanzania. (September 2022) - Machaku, Dennis; Kimolo, Mathias; Nkoronko, Mugisha; Suleman, Mujaheed; Mremi, Alex
Abstract: Introduction and importance: Urachal Mass results from a failure of obliteration of the urachal canal during fetal growth. The aetiology of urachal masses is ambiguous, being either of a cancerous or benign origin. Much literature is stipulated in children presenting with urachal-associated diseases but few in adult patients. This study aims at elucidating the existence of urachal mass with an abscess in a patient and the management modalities. Presentation of case: We present a case report of a 52-year-old female patient with a two months history of abdominal pain and discomfort associated with intermittent low-grade fevers, anorexia and marked weight loss throughout her illness. An abdominal ultrasound revealed the presence of an intra-abdominal mass. A CT scan showed a multilobulated urachal mass. She eventually had a successful operation and quick recovery postoperatively. Discussion: In the adult population, most urachal-associated diseases are malignant, with few being of benign origin. With different presentations between the two aetiologies, the most benign urachal masses may lead to infection and inflammation that typically present with a lower abdominal mass and fever. Diagnosis is made by ultrasound or CT scan of the abdomen. Surgical drainage and excision of the mass are the mainstay treatment modalities. Conclusion: Urachal masses are rare in the adult population and are often missed in initial presentations. This will constitute poor management and outcome for patients. Physicians are to be alerted of the knowledge and make a clear assessment of patients perioperatively to avoid the delayed diagnosis, which may have consequent poor outcomes. Highlights: Rarely, The Urachus may be retained as a failure of obliteration during fetal development. Associated retained urachal sinuses is a congenital anomaly that results in urachal abscesses. Urachus associated diseases are most commonly benign but may have a cancerous etiology. Poorly diagnosed patients result in poor prognosis. Early identification of the presentations with physical examinations, investigations and imaging is paramount.